Claude Lévi-Strauss structural method and its impact on the thought-world relationships (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
This article attempts an exploration in two inquiry stages of Claude Lévi-Strauss structural method. The first stage will be focused on the epistemological and methodological criteria that encrypt the analysis of kinship and myth. The second stage intends to investigate the scope of these criteria to define the category of subject and thought within the structural anthropology. Finally, an illustration of these problems is elaborated through the treatment that the structural method assigns to psychoanalytic theory.
Keywords: Structure; subject; thought; myth; kindship; unconscious